Diagnostic and statistical manual of mental disorders : DSM-IV-TR. - American Psychiatric Association; American Psychiatric Association. Task Force on DSM-IV (Washington, DC : American Psychiatric Association, 2000)
This text revision incorporates information culled from a comprehensive literature review of research about mental disorders published since DSM-IV was completed in 1994. Stay current with important updates to DSM-IV-TR. Benefit from new research into Schizophrenia, Asperger's Disorder, and other conditions. Utilize additional information about the epidemiology and other facets of DSM conditions. Updated information is included about the associated features, culture, age, and gender features, prevalence, course, and familial pattern of mental disorders. The DSM-IV-TR brings this essential diagnostic tool up-to-date, to promote effective diagnosis, treatment, and quality of care. Now you can get all the essential diagnostic information you rely on from the DSM-IV along with important updates not found in the 1994 edition.
Introduction -- Use of the manual -- DSM-IV-TR classification -- Multiaxial assessment -- Disorders usually first diagnosed in infancy, childhood, or adolescence -- Delirium, dementia, and amnestic and other cognitive disorders -- Mental disorders due to a general medical condition -- Substance-related disorders -- Schizophrenia and other psychotic disorders -- Mood disorders -- Anxiety disorders -- Somatoform disorders -- Factitious disorders -- Dissociative disorders -- Sexual and gender identity disorders -- Eating disorders -- Sleep disorders -- Impulse-control disorders not elsewhere classified -- Adjustment disorders -- Personality disorders -- Other conditions that may be a focus of clinical attention -- Additional codes -- Appendix A. Decision trees for differential diagnosis -- Appendix B. Criteria sets and axes provided for further study -- Appendix C. Glossary of technical terms -- Appendix D. Highlights of changes in DSM-IV text revision -- Appendix E. Alphabetical listing of DSM-IV-TR diagnoses and codes -- Appendix F. Numerical listing of DSM-IV-TR diagnoses and codes -- Appendix G. ICD-9-CM codes for selected general medical conditions and medication-induced disorders -- Appendix H. DSM-IV classification (with ICD-10 codes) -- Appendix I. Outline for cultural formulation and glossary of culture-bound syndromes -- Appendix J. DSM-IV contributors -- Appendix K. DSM-IV text revision advisers -- Index.
Includes index.
Prepared by the Task Force on DSM-IV and other committees and work groups of the American Psychiatric Association.
Also available via the UQ Library network as part of Stat!-ref. Primary care library.
Keywords: Mental illness -- Classification -- Handbooks, manuals, etc; Mental illness -- Diagnosis -- Handbooks, manuals, etc; Mental Disorders -- classification; Mental Disorders -- diagnosis